(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Entropy is a physical quantity associated with the expansion of the Universe and has a special force that determines the state of everything that moves. The thermodynamic and statistical definition of entropy is well known. This research report presents the informational definition of entropy as defined by Shannon, an explanation of the informational definition of entropy with simple examples, and an interpretation of the informational meaning of entropy.